Effect of Baking Temperature on Carotenoids and Provitamin A in Bread made with Mandarin (Citrus reticulata) Epicarp Extract - Luis E. Ordóñez-Santos*; Jessica Esparza-Estrada; Pedro Vanegas-Mahecha (TecnoLógicas, 2023)
Consumers are interested in products with functional properties that contribute to their well-being and health. An alternative source of functional ingredients would be the by-products of the citrus industry, which can be used as natural additives in baked products. Therefore, the objective of this study was to evaluate the effect of temperature on the concentration of carotenoids and provitamin A when baking bread in a temperature range of 160-200 ºC. We studied the thermal degradation kinetics and thermodynamic parameters of the carotenoids β-carotene, α-carotene, β-cryptoxanthin, lycopene, and provitamin A in bread dough samples made with mandarin epicarp lipid extract baked at three temperatures (160, 180, and 200 ºC). The results showed that carotenoid pigments and provitamin A are significatively reduced (p < 0.05) as baking time and temperature increase, and the degradation of bioactive compounds was set to a first-order kinetic R2 > 0.83. Thermic resistance values (z) and activation energy (Ea) during the baking process of bread showed that β-carotenes are an unstable thermal phytochemical, followed by provitamin A, α-carotenoid, lycopene, and β-cryptoxanthin. In this research, it can be concluded that the results would be important for the design and optimization of baked bread, as it will allow to maximize the levels of these micronutrients.